Combined surgical ablation with superpulsed CO2 laser for treatment of facial basel cell carcinoma - Eiad KHOURY (International Arab Journal of Dentistry (IAJD), 2020)
Basal cell carcinoma (BCC) is the most common skin cancers in face region. The most concern for surgeons is success of treatment with high cure rate and good cosmetic result. There are several methods for treatment , including laser therapy. The objectives of the present study were to evaluate the healing of wounds (recurrence and cosmetic outcome) after treatment by surgical ablation and irradiation by superpulsed mode of laser CO2.A total of 18 patients with BCC, age between 58-71 years, from both gender (7 males and 11 females) were included in the study. The tumorous mass was ablated firstly, then the tumor bed was irradiated using 5-8W Pulsed CO2 laser. The wounds were left open to secondary epithelization. Recurrence and cosmetic outcomes were observed after one year follow-up. The mean age of the participants was 66 years (range 58-71 years). The mean size (maximal diameter of lesion) was 9.3 mm (range: 7.2-11.3mm). 12 tumors (66.6%) were of the superficial type, 6 tumors (33.3%) were of the nodular type. No recurrence was observed one year after surgery. Slight scar was found in 3 cases (16.6%). There were no complications during the wound healing period .The present study showed that the surgical ablation combined with superpulsed CO2 laser is an effective option to treat BCC and to achieve high cure rates and good esthetic outcomes.